KUALITAS VISUM ET REPERTUM PERLUKAAN DI RUMAH SAKIT UMUM DAERAH BENGKALIS PERIODE 1 JANUARI 2009-31 DESEMBER 2013 - Rima Ayu Lestari; Dedi Afandi; Laode Burhauddin Mursali (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTVisum et Repertum (VeR) is a written statement of doctor who made request by the investigator is required for law enforcement and justice. VeR of injury is the type of VeR that most often requested by the investigator to a doctor. This research were done to find out the quality of VeR of injury in Bengkalis General Hospital during 1st January 2009-31st December 2013. A descriptive retrospective research was designed using Herkutanto’s scoring method with 13 unit VeR in preliminary unit of Ver, reporting unit of VeR and inference unit of VeR. All VeR data in Bengkalis General Hospital during 1st January 2009-31st December 2013 were counted as samples a two hundred forty four VeR data in Bengkalis General Hospital during 1st January 2009-31st December 2013. That were found injury survivors most cases are in the age group 22-40 years old as many as 106 victims (43,44%), mostly male 177 victims (72,54%). The most frequent violence that were experienced by the victims were blunt violence was 280 VeR (85,25%). The preliminary unit of VeR about 69,34% showed medium quality, the reporting unit about 55,09% showed medium quality and also the inference unit about 42,62% showed poor quality. It can be concluded that quality of VeR reports in Bengkalis General Hospital during 1st January 2009-31st December 2013 was 49% which means poor quality.Keywords: Visum et Repertum, injury, the quality of Visum et Repertum of injury